Biodiversity of Aquatic Insects in Good Agricultural Practices Rice Fields in Lower Northeastern - Jiaphasuanan, Tassanee; Wanchai, Pratchayaporn; Salaow, Supannika (Health Science, Science and Technology Reviews, 2020)
Good Agricultural Practices (GAP) was promoted for food agriculture system for preventing and reducing the health risk harmful. The most significant specification for GAP is non-contaminate of hazardous chemicals in water resource. The objective of this study was investigated the biodiversity of aquatic insects in GAP rice fields comparing with chemical rice fields. Aquatic insect and water quality in rice fields were investigated in lower northeastern, Sisaket, Amnat Charoen, Yasothon and Ubon Ratchathani, during March, August and December 2018. The results of aquatic insect biodiversity and distribution showed that Shannon-Wiener’s index: H’ in GAP rice field was significantly higher than chemical rice field in all sites study (p < 0.05). The most abundant of aquatic insects was found in GAP rice field at Yasothon site. Seven orders and 17 families were recorded. Hemipteran was the highest in abundance groups in the fields (7 families) followed by Odonata (3 families), Trichopteran (2 families), Coleopteran (2 families), Ephemeroptera (1 families), Dipteran (1 families) and Plecopteran (1 families). While, the least abundant was found in chemical rice field at Amnat Charoen site, 4 orders and 8 families. In addition, bio-indicator insects for good water quality were found in GAP rice fields which is consistent with the results of water quality, high dissolved oxygen and low biochemical oxygen demand.